ChemInform Abstract: Asymmetric Organocatalytic Synthesis of 4, 6‐Bis(1H‐indole‐3‐yl)‐piperidine‐2‐carboxylates. Issue 45 (23rd October 2014) - Zhong, Sabilla; Nieger, Martin; Bihlmeier, Angela; Shi, Min; Braese, Stefan
Abstract Only 3‐vinylindoles afford the products (III) and (V), whereas the reaction of 2‐vinylindole gives the amino acid derivative (VII).